2021
DOI: 10.18632/aging.203268
|View full text |Cite
|
Sign up to set email alerts
|

Methylation silencing CDH23 is a poor prognostic marker in diffuse large B-cell lymphoma

Abstract: Cadherin-23(CDH23) mediates homotypic and heterotypic cell-cell adhesions in cancer cells. However, the epigenetic regulation, the biological functions, the mechanisms and the prognostic value of CDH23 in diffuse large B-cell lymphoma (DLBCL) are still unclear. The Gene Expression Profiling Interactive Analysis (GEPIA) and the Gene Expression Omnibus (GEO) database were employed to analyze the CDH23 expression level in DLBCL. The correlation of CDH23 expression and methylation was analyzed by LinkedOmics datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Systemic expression of the four key retinal cadherins (Table 1) underlying the monogenic retinal cadherinopathies may explain their contribution to other non-ocular diseases. CDH23 has been implicated in the development of familial and sporadic pituitary adenoma (Zhang et al, 2017), as a poor prognostic marker in forms of cancer (Cao et al, 2021), and in the susceptibility to Schizophrenia (Balan et al, 2021). Similarly, PCDH15 variants have been implicated as a poor prognostic marker in ocular adnexal sebaceous carcinoma (Xu et al, 2020b), copy number variants and rare SNP with psychiatric disorders (Ishii et al, 2019, Ishizuka et al, 2016, and SNPs with hyperlipidaemia (Huertas-Vazquez et al, 2010).…”
Section: Retinal Cadherins: Uncertaintiesmentioning
confidence: 99%
“…Systemic expression of the four key retinal cadherins (Table 1) underlying the monogenic retinal cadherinopathies may explain their contribution to other non-ocular diseases. CDH23 has been implicated in the development of familial and sporadic pituitary adenoma (Zhang et al, 2017), as a poor prognostic marker in forms of cancer (Cao et al, 2021), and in the susceptibility to Schizophrenia (Balan et al, 2021). Similarly, PCDH15 variants have been implicated as a poor prognostic marker in ocular adnexal sebaceous carcinoma (Xu et al, 2020b), copy number variants and rare SNP with psychiatric disorders (Ishii et al, 2019, Ishizuka et al, 2016, and SNPs with hyperlipidaemia (Huertas-Vazquez et al, 2010).…”
Section: Retinal Cadherins: Uncertaintiesmentioning
confidence: 99%
“…Although the role of CDH23 in cancer progression and prognosis has been illustrated earlier [ 18 , 27 ], systematic and comprehensive analysis of its role in AML using bioinformatics tools has not yet been conducted. We first explored the association between CDH23 mRNA expression level and prognosis of AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cadherin-23 (CDH23) is defined as an atypical cadherin and dysregulation of CDH23 expression remarkably disrupts homotypic and heterotypic adhesions and increases the metastatic potential of various tumors [ 12 17 ]. Furthermore, the downregulation of CDH23 expression was significantly association with poorer outcome in patients with diffuse large B cell lymphoma [ 18 ]. However, the role of CDH23 in AML remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that CDH23 played a critical role in cancer progression. For instance, CDH23 was upregulated in breast cancer and was associated with the early metastasis 30 , methylated depletion of CDH23 was related with poor prognosis in Diffuse large B-cell lymphoma (DLBCL) 31 , germline mutations of CDH23 were linked with both familial and sporadic pituitary adenoma 32 . LRP1 (Low density lipoprotein receptor-related protein 1, also known as CD91) is a ubiquitously expressed endocytic receptor belonging to the low-density lipoprotein receptor (LDLR) superfamily, of which LRP1 is the most multifunctional one 33 .…”
Section: Discussionmentioning
confidence: 99%